2017
DOI: 10.1007/s00294-017-0740-5
|View full text |Cite
|
Sign up to set email alerts
|

MybA, a new player driving survival of the conidium of the human pathogen Aspergillus fumigatus

Abstract: Aspergillus fumigatus is an opportunistic human pathogen that causes various complications in patients with a weakened immune system functions. Asexual spores of A. fumigatus are responsible for initiation of aspergillosis. Long-term viability and proper germination of dormant conidia depend on trehalose accumulation, which protect the spores against thermal and oxidative stress. A putative Myb transcription factor, MybA has been recently found to be responsible for a variety of physiological and molecular rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Our results found that genes responsible for intracellular trehalose production were downregulated in ΔBbcmr1 , and the content of intracellular trehalose was also reduced. We supposed that the decreased viability and significantly increased susceptibility of ΔBbcmr1 conidia to stressors could be partially attributed to trehalose changes, as observed in other filamentous fungi ( 45 , 47 , 48 ).…”
Section: Discussionmentioning
confidence: 87%
“…Our results found that genes responsible for intracellular trehalose production were downregulated in ΔBbcmr1 , and the content of intracellular trehalose was also reduced. We supposed that the decreased viability and significantly increased susceptibility of ΔBbcmr1 conidia to stressors could be partially attributed to trehalose changes, as observed in other filamentous fungi ( 45 , 47 , 48 ).…”
Section: Discussionmentioning
confidence: 87%
“…One of the fundamental functions of fungal photoreception is self-defense against the harmful effects of UV light. Fungal spores are densely packed with protective pigments and osmolytes which protect the next generation of fungi from stressors such as UV light and oxidative stress [31][32][33]. The second fundamental function of photoreception is possibly to find optimum conditions or time for spore dispersal [34,35].…”
Section: Fungal Light Responsesmentioning
confidence: 99%